2013
DOI: 10.1063/1.4818112
|View full text |Cite
|
Sign up to set email alerts
|

A measurement of the muon-induced neutron yield in lead at a depth of 2850 m water equivalent

Abstract: Articles you may be interested inMeasurement of the muon-induced neutron yield in liquid scintillator and stainless steel at LNGS with the LVD experiment AIP Conf. A time-gating scintillation detector for the measurement of laser-induced fast neutrons Rev. Sci. Instrum. 80, 063303 (2009); 10.1063/1.3152212 Neutron Capture and Transmission Measurements on 103Rh Down to Thermal Energies AIP Conf. Proc. 769, 953 (2005); 10.1063/1.1945162 Secondary-neutron-yield measurements by current-mode detectors Rev. Sci. Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The mean excitation energy of the scintillating medium, I, is used in the Voltz et al model (see eqn (6)) to calculate the fraction of singlet excitation produced outside of the particle track. Values for this parameter were obtained using the Particle Data Group library.…”
Section: Mean Excitation Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The mean excitation energy of the scintillating medium, I, is used in the Voltz et al model (see eqn (6)) to calculate the fraction of singlet excitation produced outside of the particle track. Values for this parameter were obtained using the Particle Data Group library.…”
Section: Mean Excitation Energymentioning
confidence: 99%
“…When protons or other heavy charged particles deposit energy in organic scintillators, high excitation and ionization densities result in a reduction in scintillation efficiency-a phenomenon known as ionization quenching. While extensive research has been conducted on the response of organic scintillators to recoil nuclei, [1][2][3][4][5][6][7][8][9][10][11][12][13] there remains disagreement regarding the impact of the nature of the ionizing particle on the specific luminescence. The canonical Birks model is often used to describe the ionization quenching effect though it has failed to predict the scintillation response at low recoil energies and for particles of different charge.…”
Section: Introductionmentioning
confidence: 99%
“…This technique provides a smoothly varying function that covers the broad range of neutron energies used in this work. Recent work [49] has shown that there may be significant deviations from fits of Ref. [44] for plastic scintillator at low-energy recoils.…”
Section: Energy Reconstruction and Responsementioning
confidence: 99%
“…By applying energy and momentum conservation the maximum recoil energy of the carbon nucleus can be determined as a function of neutron energy for fully back scattered neutrons (θ n = 180 • ). However, at low detection thresholds, light yield induced by elastically scattered carbon nuclei (recoils) contributes significantly to the total light yield induced in the scintillator[29]. VANDLE is capable of running with thresholds low enough to identify and measure the light yield response curve for these carbon recoils.…”
mentioning
confidence: 99%